Konseptualisasi Media Pembelajaran Bahasa Arab Berbasis Android Berdasarkan Analisis Kebutuhan Kurikulum Lokal Pondok Pesantren DDI Kassi Jeneponto - Sitti Saenab; Hamsar Hamsar; Muhammad Firdaus; Sudarni Sudarni (JPPI (Jurnal Pendidikan Islam Pendekatan Interdisipliner), 2025)
Despite the rapid growth of Android-based learning media, previous studies have largely developed generic applications that are not aligned with the characteristics of local Islamic boarding school curricula, creating a research gap in curriculum-specific conceptual models for Arabic language learning. This study aims to formulate a conceptual framework for Android-based Arabic learning media that is aligned with the local curriculum of DDI Kassi Islamic Boarding School, Jeneponto. This research employed a library research approach using qualitative content analysis. Data were obtained from curriculum documents, syllabi, Arabic textbooks used in the pesantren, institutional regulations, and relevant scientific publications. The content analysis was conducted through document identification, categorization, interpretation, and synthesis to formulate the conceptual architecture of the proposed learning media. The findings indicate that the local curriculum emphasizes the integration of Qawaid (Arabic grammar) and Hiwar (practical conversation), which are translated into four principal application components: interactive digital texts with Harakat On/Off features, native-speaker pronunciation audio, gamified self-assessment (Ikhtibar), and a fully offline learning system compatible with pesantren regulations. The novelty of this study lies in proposing a local-curriculum-driven conceptualization that integrates traditional pesantren learning practices with Android technology without diminishing the educational authority of the kiai and ustaz. Practically, the proposed blueprint can serve as a reference for developing contextual Arabic learning applications in Islamic boarding schools, while academically it enriches the implementation of Mobile-Assisted Language Learning (MALL) within the context of locally based Islamic education.